Anaiysis of cosmic mysticm from the perspective of sects - Abdul Rahman Najafi Imran (مطالعات تطبیقی فقه و اصول مذاهب, 2020)
Background and Aim: Many false mystics have appeared for a long time and continue to do so today, and it continues with the two goals of "confronting the divine religions, especially Islam" and "filling the feeling of spiritual emptiness in the Western world." Because on the one hand, the tendency towards divine religions, especially Islam, is spreading in the world, and on the other hand, the Western world has reached a dead end and the feeling of spiritual emptiness has been revived in it, so to deal with it, the emergence of emerging anti-religious mysticism It is said that one of them is "cosmic mysticism" or "ring mysticism" and it is necessary to study it from the perspective of Islam and the ruling of each of the tenants and promoters of ring mysticism, absorption and joining cosmic mysticism and publishing and preserving And studied its works from the perspective of the sects, which is addressed in the present article, and by contemplating the rules of jurisprudence accepted by each of the Shiites and Sunnis, it was proved that each of the attraction and tendency, ownership and promotion and publication. And preserving the works of mysticism is forbidden. Materials and Methods: The present study, based on expressing the views and beliefs of the school of cosmic mysticism and criticizing and examining it from the perspective of jurisprudential rules and in a library manner, has dealt with the present issue. Conclusion: The school of cosmic mysticism or ring mysticism was established in Iran in the eighties, and for this reason, its jurisprudential study has not been much discussed and requires the ruling of each of the preservation and publication of works and attraction to such a school and also It should be argued that holding and promoting the school of cosmic mysticism is forbidden due to the sanctity of heresy and legislation and the rule of denying the mustache, and being absorbed and joining the mysticism of the circle is also forbidden and three reasons: The correct beliefs and reasons for the need to acquire the right behaviors, show its sanctity. Just as the rule of sanctity forbids the preservation of errant books, any preservation, publication and study of the works of cosmic mysticism is forbidden.